1990
DOI: 10.1111/j.1476-5381.1990.tb12717.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies of human erectile tissue: characteristics of spontaneous contractions and alterations in α‐adrenoceptor responsiveness with age and disease in isolated tissues

Abstract: 1 The pathophysiology of impotence related to vascular smooth muscle dysfunction in the male corpus cavernosum was studied on human isolated erectile tissue (HET). Studies were conducted on 140 sections of HET obtained from 38 male patients undergoing surgery for implantation of penile prostheses to correct underlying erectile dysfunction. 2 Spontaneous myotonic oscillations were characteristic of greater than 90% of all HET preparations at 37°C. These spontaneous oscillations were markedly attenuated by indom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
7

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(76 citation statements)
references
References 28 publications
6
62
0
7
Order By: Relevance
“…15,28,31,59 In the absence of detailed biochemical and molecular biological analyses of the alpha-2 adrenergic receptors expressed in corpus cavernosum tissue and their functional activities, it remains unclear if alpha-2 adrenergic receptors are expressed in the corpus cavernosum tissue and if these receptors are physiologically functional.…”
Section: Classi®cation Of Alpha-adrenergic Receptor Subtypes In Humanmentioning
confidence: 99%
“…15,28,31,59 In the absence of detailed biochemical and molecular biological analyses of the alpha-2 adrenergic receptors expressed in corpus cavernosum tissue and their functional activities, it remains unclear if alpha-2 adrenergic receptors are expressed in the corpus cavernosum tissue and if these receptors are physiologically functional.…”
Section: Classi®cation Of Alpha-adrenergic Receptor Subtypes In Humanmentioning
confidence: 99%
“…In vitro studies of CSM from men diagnosed with organic erectile dysfunction (ED) have suggested that the response to phenylephrine (PE) is different between young and old men. 4 The CSM from older men experienced a signi®cantly greater degree of PE-induced contractions than that for younger men. 4,5 The cellular and molecular mechanism of this phenomenon, however, is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…4 The CSM from older men experienced a signi®cantly greater degree of PE-induced contractions than that for younger men. 4,5 The cellular and molecular mechanism of this phenomenon, however, is still unknown. In this regard, several studies have shown that altered expression of growth factors is associated with development and aging.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this ®nding, basal adrenergic tone has been reported to increase in aging men with erectile dysfunction. 7,8 This experimental ®nding is further supported by the endogenous synthesis of PGE by the corpus cavernosum during penile erection. 6 The frequency and duration of nocturnal penile tumescence (1.5± 3 hasleep period) may provide a daily oxygenation and production of vasoactive factors which modulate expression of functional receptors in the corpus cavernosum.…”
Section: Discussionmentioning
confidence: 72%